2020
DOI: 10.7150/jca.36498
|View full text |Cite
|
Sign up to set email alerts
|

High CXCR4 Expression Predicts a Poor Prognosis in Resected Lung Adenosquamous Carcinoma

Abstract: Background: Primary adenosquamous carcinoma (ASC) is a rare malignant tumor in the lung and its biological behavior has not yet been thoroughly described. In this study, we aimed to explore the clinical and biological role of CXCR4 in patients with resected lung ASC. Methods: We retrospectively reviewed the clinical records of patients with histologically confirmed lung ASC who underwent surgical resection with systematic lymph node dissection. Immunohistochemical staining was performed to detect the expressio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 31 publications
(32 reference statements)
0
9
0
Order By: Relevance
“…Fourteen out of 27 studies including 1899 patients with lung cancer evaluated the association between CXCR4 expression and overall survival (OS) [ 12 15 , 17 26 ]. The pooled HR showed that high CXCR4 expression was linked to decreased OS in lung cancer (HR 1.61, 95% CI 1.42–1.82, P < 0.001, I 2 = 32.2%) (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Fourteen out of 27 studies including 1899 patients with lung cancer evaluated the association between CXCR4 expression and overall survival (OS) [ 12 15 , 17 26 ]. The pooled HR showed that high CXCR4 expression was linked to decreased OS in lung cancer (HR 1.61, 95% CI 1.42–1.82, P < 0.001, I 2 = 32.2%) (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, only 3 studies including 555 patients with resected lung cancer were enrolled to pool the HR for DFS [ 13 , 26 , 27 ]. All patients were treated with initial surgical resection.…”
Section: Resultsmentioning
confidence: 99%
“…CXCR4 belongs to the G protein-coupled receptor superfamily and is expressed in a cortical protein-dependent manner on the cell surface ( Teicher & Fricker, 2010 ). CXCR4 has been reported to be overexpressed in a variety of tumor cells and is involved in tumor proliferation, invasion, metastasis, and worse prognosis ( Ottaiano et al, 2020 ; Wang et al, 2020a ; Zhu et al, 2020 ). GTP-binding protein overexpressed in skeletal muscle (GEM) is a GTPase originally identified in mitogen-stimulated T lymphocytes and v-Abl-transformed pre- B cells and is highly expressed in the spleen, thymus, and kidneys ( Cohen et al, 1994 ; Huang et al, 2014 ).…”
Section: Discussionmentioning
confidence: 99%
“…The high expression of CXCR4 promotes the aggressiveness of tumor cells, enhances chemoresistance and inhibits cell apoptosis. Clinically, high CXCR4 expression may be related to the poor prognosis of lung cancer patients (Zhu et al, 2020). It has been reported that the CXCR4-inhibiting nanocomplex reduces tumor fibrosis and promotes cytotoxic T lymphocytes penetration, regulating the lung immune response, thereby further enhancing the anti-PD-L1 immune response (Li et al, 2020b).…”
Section: Introductionmentioning
confidence: 99%